Imaging for concealed weapon detection a tutorial overview of development in imaging sensors and processing. - Hua-Mei Chen (IEEE Signal processing magazine)
Manual screening procedures for detecting concealed weapons such as handguns, knives, and explosives are common in controlled access settings like airports, entrances to sensitive buildings, and public events. The detection of weapons concealed underneath a person's clothing is an important obstacle to the improvement of the security of the general public as well as the safety of public assets like airports and buildings. It is desirable to be able to detect concealed weapons from a standoff distance, especially when it is impossible to arrange the flow of people through a controlled procedure. The goal is the eventual deployment of automatic detection and recognition of concealed weapons. It is a technological challenge that requires innovative solutions in sensor technologies and image processing. A number of sensors based on different phenomenology as well as image processing support are being developed to observe objects underneath people's clothing. The main aim of this article is to provide a tutorial overview of these developments.